Asociación entre hipoalbuminemia y mortalidad en adultos mayores hospitalizados, Hospital Regional Loreto, 2021-2023 - Pérez Alván, Jeanette Madeleyne (2025)
Hypoalbuminemia, characterized by low serum albumin levels, is a crucial biological marker in geriatric patients, reflecting both nutritional status and the degree of systemic inflammation. In hospitalized older adults, its prevalence is associated with various chronic and acute pathologies, and previous studies have demonstrated its relationship with worse clinical outcomes, including an increased risk of mortality. For this reason, the present study aims to determine the association between hypoalbuminemia and mortality in hospitalized older adults at the Hospital Regional Loreto during the period 2021-2023. To achieve this, an observational-analytical, cross-sectional, and retrospective study was conducted. The sample included 152 patients over 60 years of age, of whom 70.4% had serum albumin levels lower than 3.4 g/dL. Data analysis showed that hypoalbuminemia was significantly associated with a higher risk of in hospital mortality, with an OR of 2.7 (95% CI: 1.3 – 5.5). Additionally, prevalent comorbidities such as hypertension, diabetes mellitus, and anemia were observed in this population. In conclusion, hypoalbuminemia is an independent prognostic factor for mortality in hospitalized older adults, highlighting the importance of its early identification and management in this vulnerable group.